1994
DOI: 10.1116/1.579155
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of titanium nitride thin films deposited at low temperatures using direct current magnetron sputtering

Abstract: Articles you may be interested inNumerical investigation via three-dimensional Monte Carlo modeling of sputtering and deposition processes in a direct current unbalanced magnetron discharge Low temperature, fast deposition of metallic titanium nitride films using plasma activated reactive evaporation J. Vac. Sci. Technol. A 23, 394 (2005); 10.1116/1.1874152 Structure and mechanical properties of Ti-Si-N films deposited by combined DC/RF reactive unbalanced magnetron sputtering Deposition and properties of yttr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 0 publications
1
19
1
Order By: Relevance
“…[1][2][3][4][5] These studies have suggested that epitaxial TiN films have superior effectiveness as corrosion-resistant coatings and diffusion barriers to that of polycrystalline TiN films. 1 Thus, properties of polycrystalline TiN have been studied in connection with the atomic concentration ratio ͑N/Ti͒ and microstructures in many previous papers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] These studies have suggested that epitaxial TiN films have superior effectiveness as corrosion-resistant coatings and diffusion barriers to that of polycrystalline TiN films. 1 Thus, properties of polycrystalline TiN have been studied in connection with the atomic concentration ratio ͑N/Ti͒ and microstructures in many previous papers.…”
Section: Introductionmentioning
confidence: 99%
“…This class of materials is interesting because they have conductivities ͑thermal and electrical͒ comparable to those of the transition metals while their hardness, inertness, and high melting points are more typical of covalently bonded materials. High quality films are easily deposited using dc or rf reactive magnetron sputtering systems [9][10][11][12][13] and might be used for coating Mo or Si emitter arrays 1 to improve their performance, or for forming emitter arrays directly ͑e.g., via a Spindt type process 14 ͒. [4][5][6][7] For vacuum microelectronics applications, however, emitter fabrication schemes compatible with current thin film processes are required.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] This phenomenon is explained by atomic peening in which highenergy particles are reflected at the target and bombard the growing films. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] This phenomenon is explained by atomic peening in which highenergy particles are reflected at the target and bombard the growing films.…”
Section: Introductionmentioning
confidence: 99%